Залежність ударостійкості від швидкості розповсюдження хвиль в літійалюмосилікатних склокристалічних матеріалах - Саввова, Оксана Вікторівна; Топчий, Віталій Леонідович; Рябінін, Святослав Олександрович; Кураш, Леонід Степанович; Тимофєєв, Вадим Дмитрович (НТУ "ХПІ", 2017)
Проаналізовано ударно-хвильова стадія взаємодії матеріалу ударника та перешкоди у аспекті створення ударостійких броне елементів. Визначено актуальність створення захисних склокристалічних матеріалів з урахуванням особливостей їх структури. Встановлено залежність швидкості розповсюдження звукових хвиль в алюмосилікатних стеклах з урахуванням питомої енергії атомізації оксидів та в склокристалічних матеріалах на їх основі в залежності від їх пружних властивостей та щільності. За критерієм ударостійкості проведено оцінку придатності розроблених склокристалічних матеріалів на основі β сподумену та дисилікату літію щодо їх використання як елементів бронезахисту.

The shock-wave stage of interaction between the impactor material and obstacles in the aspect of creating impact-resistant armor elements is analyzed. The actuality of creation of protective glass-crystalline materials is determined, taking into account the features of their structure. The prospect of using lithium-aluminosilicate glass-ceramic materials with high indicators of sound wave propagation as shock-resistant elements of armor protection is established and the choice of glass of the generating system is justified. The dependence of the speed of propagation of sound waves in aluminosilicate glasses is determined taking into account the specific energy of atomization of oxides and into glass- ceramic materials based on them, depending on their elastic properties and density. According to the impact criterion, an assessment was made of the suitability of the developed glass- ceramic materials based on β-spodumen and disilicate in relation to their use as armored protection elements. It has been established that the presence of crystalline and amorphous phases with different elastic properties in glass crystalline materials allows to provide more effective destruction of the shock absorber and to minimize post-percutaneous action. These results can be used in the development of armored elements with high bullet resistance.
Dependence of shock resistance from the speed of wave spreading in lithium-aluminous glass-ceramic materials
Keywords: ударостійкість; швидкість розповсюдження хвиль; бронеелемент; impact resistance; wave propagation velocity; armor-iron